Calcium enrichment in sea spray aerosol particles - M. E. Salter; E. Hamacher‐Barth; C. Leck; J. Werner; C. M. Johnson; I. Riipinen; E. D. Nilsson; P. Zieger (Geophysical Research Letters)
Abstract Sea spray aerosol particles are an integral part of the Earth's radiation budget. To date, the inorganic composition of nascent sea spray aerosol particles has widely been assumed to be equivalent to the inorganic composition of seawater. Here we challenge this assumption using a laboratory sea spray chamber containing both natural and artificial seawater, as well as with ambient aerosol samples collected over the central Arctic Ocean during summer. We observe significant enrichment of calcium in submicrometer (<1 μm in diameter) sea spray aerosol particles when particles are generated from both seawater sources in the laboratory as well as in the ambient aerosols samples. We also observe a tendency for increasing calcium enrichment with decreasing particle size. Our results suggest that calcium enrichment in sea spray aerosol particles may be environmentally significant with implications for our understanding of sea spray aerosol, its impact on Earth's climate, as well as the chemistry of the marine atmosphere.